Two new conjectures concerning positive jacobi polynomials sums (1998)
[Formula Matemática] hold, is stated. An algorithm for checking the new conjecture using the package Mathematica is provided. Numerical results in support of the conjecture are given and a possible approach to its proof is sketched.